Is vaccination good value for money? A review of cost-utility analyses of vaccination strategies in eight European countries - Marco Barbieri; Stefano Capri (Epidemiology, Biostatistics and Public Health)
Objective: The objective of this study is to review published cost-utility analyses of vaccination strategies in eight European countries and to assess whether there are differences in cost-effectiveness terms among countries and vaccinations.